Localised Learning in Rural School Context: Problems and Prospects - Jena, Prajnya Paramita (INDIAN EDUCATIONAL REVIEW, 2013)
Although the approach of localised learning being advocated in school curriculum frameworks, its implementation has not been widespread. Nonetheless, localised learning tends for the most part to be dominated by issues, while the method of making learning localised remain comparatively neglected. Considering the issue of low quality of school education, particularly in rural areas, it is presumed that only the teachers with positive motivation, skill and professionalism can make the localised learning successful with the availability of proper educational resources. This paper interprets the concept of localised learning and presents the author’s own past experience as a rural school teacher as well as her identification of different issues that constrains localised learning and views on the roadmap for implementing localised learning.